changes - Grigoryeva, Elena (project baikal, 2022)
This year has brought many changes in different parts of the world: here it has caused a stir on the land, and there it has calmed it down; here a luminary has set, there another one has begun to shine; here the world has learnt a new mystery of being, and there dwellings and generations have crumbled into ash. I. Goncharov. Oblomov If we continue the classic’s tirade, it should be noted that one of the changes has embraced not just separate parts, but the entire world. And that, of course, is the pandemic, with its insistent attempts to limit our freedoms, to force communication into the narrow confines of virtuality, and to change our way of life in general. Pandemic powerfully draws everyone’s attention, even from total digitalization and other progress. We confess immediately and frankly: we do not hope to cover the subject, it is too huge. What we put on the cover is not a claim to an exhaustive analysis of the topic, but rather a key word of the issue. So, CHANGES. The Russian government is putting forward a draft of the Eastern Turn. Its possible significance for the eastern regions of the country and for Irkutsk in particular is discussed by the members of the discussion club of pb (24). Another important and hotly debated change is related to global warming and its implications for geopolitics. To what extent does this time of change repeat a previous similar period in the middle of the last century? What mistakes were made, what opportunities were not seized, and what can we now learn from past experiences? Academicians Kudryavtsev and Bokov (58) reflect on the changes that caused a significant stir in national architecture in the 1950s and 1960s. Although pushed aside from the forefront, digitalization continues to promise a variety of wonders. We are in for multiclouds, 6G, holographic and haptic communications, virtual doubles and the primacy of artificial intelligence. Such things as unprecedented phenomena of digital nomads will appear. How ready are we for this? Our permanent author Peter Kapustin (32) asks a fateful question: will architecture together with the whole civilization dissolve in the accelerating stream of uncontrollable changes, or will it reassert itself as a full-fledged sphere of life, a bearer of civilization values?